THE EFFECT OF LACTIC ACID BACTERIA AND DIFFERENT LEVEL OF CARBOHYDRATE SOURCES ADDITION ON TOFU WASTE INDUSTRY FERMENTATION - Zaenal Bachruddin (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
A The purpose of this research was to figure out the affinity value of soluble carbohydrates from pollard with lactic acid bacteria (LAB) and its effect on tofu waste silage. Lactic acid bacteria (LAB) isolates used as inoculum were commerce LAB isolates (B13-1) and yolk LAB isolates (K6-3). The selected of LAB isolates used in the tofu waste silage were tofu waste (TW) and pollard (P) with different proportion (70:30), (60:40), and (55:45). The result showed that the addition of soluble carbohydrates sources in the tofu waste silage did not affect lactic acid and pH value. However LAB addition significantly increased lactic acid (P<0.05). The TW:P proportion (55:45) produced the highest lactic acid concentration with the value of 3.54%DM with pH value 3.90. Proportion of TW:P gave significantly different effect on dry matter (DM) and organic matter (OM) (P<0.01). Meanwhile, LAB addition presented significant difference in declining of dry matter percentage (P<0.01) but it showed non-significant effect on organic matter percentage from the tofu curd silage. It can be concluded that pollard addition with the value of 45% shows that tofu waste silage has the highest lactic acid concentration and ideal pH value.